2023
DOI: 10.1186/s13045-023-01453-1
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid metabolism in immune cells: essential regulators of the effector functions, and promising opportunities to enhance cancer immunotherapy

Luming Yang,
Zhaole Chu,
Meng Liu
et al.

Abstract: Amino acids are basic nutrients for immune cells during organ development, tissue homeostasis, and the immune response. Regarding metabolic reprogramming in the tumor microenvironment, dysregulation of amino acid consumption in immune cells is an important underlying mechanism leading to impaired anti-tumor immunity. Emerging studies have revealed that altered amino acid metabolism is tightly linked to tumor outgrowth, metastasis, and therapeutic resistance through governing the fate of various immune cells. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(21 citation statements)
references
References 354 publications
(399 reference statements)
0
21
0
Order By: Relevance
“…[27][28][29] Amino acid metabolism also influences the production of pro-inflammatory cytokines, such as IL-17 and TNFα, which are key drivers of inflammation in psoriasis. 30 Addiationally, amino acids can modulate the activity of immune cells, such as T cells and dendritic cells, which are implicated in the pathogenesis of psoriasis. In our study, we observed a significant upregulation of phenylalanine, tyrosine, tryptophan, and arginine metabolism pathways in psoriatic patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Amino acid metabolism also influences the production of pro-inflammatory cytokines, such as IL-17 and TNFα, which are key drivers of inflammation in psoriasis. 30 Addiationally, amino acids can modulate the activity of immune cells, such as T cells and dendritic cells, which are implicated in the pathogenesis of psoriasis. In our study, we observed a significant upregulation of phenylalanine, tyrosine, tryptophan, and arginine metabolism pathways in psoriatic patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that kyureninase, the key enzyme of tryptophan metabolism, is significantly overexpressed in psoriasis, contributing to the disease onset by affecting the proliferation of keratinocytes and the secretion of inflammatory cytokines 27–29 . Amino acid metabolism also influences the production of pro‐inflammatory cytokines, such as IL‐17 and TNF‐α, which are key drivers of inflammation in psoriasis 30 . Addiationally, amino acids can modulate the activity of immune cells, such as T cells and dendritic cells, which are implicated in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine is metabolized mainly by arginase-1 (Arg1) and nitric oxide synthase (NOS) in myeloid cells. The review by Yang et al [34] noted that studies have observed that reducing arginine in the human body attenuates the function and proliferation of T cells, which can be reversed by arginine supplementation. Furthermore, under arginine restriction, T cells downregulate CD3ζ expression, preventing TCR (T-cell receptor) expression, leading to reduced proliferation and cytokine secretion.…”
Section: Argininementioning
confidence: 99%
“…Furthermore, under arginine restriction, T cells downregulate CD3ζ expression, preventing TCR (T-cell receptor) expression, leading to reduced proliferation and cytokine secretion. Arginine transporter, cationic amino acid transporter-1 (CAT1), supports naive and memory CD4 + T cells and CD8 + T cells to maintain T-cell proliferation and activation [34].…”
Section: Argininementioning
confidence: 99%
“… 10 Furthermore, it has been shown that amino acid metabolism could strongly influence the tumor therapy resistance by controlling the destiny of diverse immune cells. 11 That is to say, metabolism process in cancer cells and immune cells might be different, and the metabolism pathways in TIME are complexed and need to perform further researches.…”
Section: Introductionmentioning
confidence: 99%